ANALISIS PENERAPAN HAK IMUNITAS ANGGOTA DPR DALAM TINDAK PIDANA UJARAN KEBENCIAN DI MEDIA SOSIAL - Lutfiah Nur Zahra (2023)
Members of the DPR are representatives of the people who are elected by the people, members of the DPR have the right of immunity to be free in expressing opinions in carrying out their duties and authorities, and members of the DPR cannot be sued criminally or civilly for carrying out their duties and authorities. Advances in technology make developments in parliament more extensive. In the case that ensnared Arteria Dahlan in a joint working meeting with the Attorney General, it illustrates that there is a vacuum in the limits of immunity rights and also social media regulations in Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, and the Regional Representative Council. This study uses normative research, with a statutory and conceptual approach. This research found that Arteria Dahlan could not be convicted of hate speech crimes due to the inherent right of immunity, so a new policy was needed regarding the limitation of immunity rights and the addition of clauses related to social media in Law Number 17 of 2014 concerning the People's Consultative Assembly, the Representative Council People, and the Regional Representative Council. This is intended to patent limits on immunity rights that bind members of the DPR and social media.